Learning Commons and university libraries: spaces for learning in the Library System of the Tecnológico of Costa Rica - Gómez-Valverde, Lidia Yiseth (2024)
Currently, there is a tendency in university libraries to provide services in physical and virtual spaces where the user has infrastructure and guidance to meet their information needs through library and technological services, spaces for collaborative work required for the fulfillment of their academic and research activities. This concept is known as Learning Commons, which is a set of information services using communication technologies in a mixture of physical, electronic, socio-humanistic, and cultural resources in order to strength the teaching learning and research processes, seeking an effective organization and management of resources, as well as optimization of space. The purpose of this article is to develop the didactic and administrative characteristics for the implementation of a learning commons, considered as a new space to “do and learn”, active for social gathering, a space where you can find and access technology, where you can explore and collaborate, with access to digital resources such as books, journals, standards, protocols, among others. Finally, a brief description of the SIBITEC will be made since many of the characteristics of this scheme allow it to be a model to other information centers.